Manajemen PAUD - Nabila, Restu; Tri Utami, Dian (Generasi Emas, 2023)
This research was conducted with the background of government policy demands regarding the management of PAUD standards. The implementation of PAUD management is one of the benchmarks of success of an ongoing PAUD institution. Therefore, good PAUD management will be able to realize a quality PAUD institution. This research is a descriptive qualitative study conducted in PAUD Sekato, Marison Village, Minas District, Siak Regency. The purpose of this research is to describe in general the implementation of PAUD management. This study uses qualitative research methods aimed at field research. The type of data used is data obtained from observations, interviews, and documentation. The results showed that the management of Sekato PAUD has not been fully implemented, but there are supporting and inhibiting factors that influence the management of PAUD management.